2011
DOI: 10.1097/rhu.0b013e31821c0310
|View full text |Cite|
|
Sign up to set email alerts
|

Double-Blind, Randomized, Controlled, Pilot Study Comparing Classic Ayurvedic Medicine, Methotrexate, and Their Combination in Rheumatoid Arthritis

Abstract: In this first-ever, double-blind, randomized, placebo-controlled pilot study comparing Ayurveda, MTX, and their combination, all 3 treatments were approximately equivalent in efficacy, within the limits of a pilot study. Adverse events were numerically fewer in the Ayurveda-only group. This study demonstrates that double-blind, placebo-controlled, randomized studies are possible when testing individualized classic Ayurvedic versus allopathic treatment in ways acceptable to western standards and to Ayurvedic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 10 publications
0
43
0
4
Order By: Relevance
“…This was also possible with funds from the Government. Another such notable study is on rheumatoid arthritis using integrative medicine 24 . Such instances addressing public health issues through integration should encourage the Government to promote similar attempts.…”
Section: Researchmentioning
confidence: 99%
“…This was also possible with funds from the Government. Another such notable study is on rheumatoid arthritis using integrative medicine 24 . Such instances addressing public health issues through integration should encourage the Government to promote similar attempts.…”
Section: Researchmentioning
confidence: 99%
“…Moreover, a recent pilot trial on traditional Indian medicine found comparable effects of individualized ayurvedic medicine and methotrexate 3 . There is controversy about the role of nutrition in rheumatology.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Several publications describe the integration of CAM with biomedicine, albeit with a low number of patients, and minimum details on how they used medicines. Such studies rely heavily on 'pragmatic' trials 4 . Some lack an algorithm or internationally accepted protocol items for replication 5 .…”
Section: Introductionmentioning
confidence: 99%